2017
DOI: 10.3945/ajcn.117.156083
|View full text |Cite
|
Sign up to set email alerts
|

Integrating themes, evidence gaps, and research needs identified by workshop on iron screening and supplementation in iron-replete pregnant women and young children

Abstract: This report addresses the evidence and the uncertainties, knowledge gaps, and research needs identified by participants at the NIH workshop related to iron screening and routine iron supplementation of largely iron-replete pregnant women and young children (6-24 mo) in developed countries. The workshop presentations and panel discussions focused on current understanding and knowledge gaps related to iron homeostasis, measurement of and evidence for iron status, and emerging concerns about supplementing iron-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 62 publications
0
27
0
1
Order By: Relevance
“…The prospect for developing standard reference methods for SF and sTfR is poor because of the size of the proteins involved and technical challenges inherent in doing so [ 46 , 47 ]. In the absence of such standardization, measures may exhibit imprecision and inflated Confidence Intervals [ 46 , 48 ] that can create interpretative challenges and also contribute to misclassification of ID and IDA.…”
Section: Iron Status: Uncertainties In Assessment Of Pregnant Womementioning
confidence: 99%
See 2 more Smart Citations
“…The prospect for developing standard reference methods for SF and sTfR is poor because of the size of the proteins involved and technical challenges inherent in doing so [ 46 , 47 ]. In the absence of such standardization, measures may exhibit imprecision and inflated Confidence Intervals [ 46 , 48 ] that can create interpretative challenges and also contribute to misclassification of ID and IDA.…”
Section: Iron Status: Uncertainties In Assessment Of Pregnant Womementioning
confidence: 99%
“…A number of knowledge gaps and research needs were identified at the NIH Workshop on Iron Screening and Supplementation of Iron-Replete Pregnant Women and Young Children in 2016. Four major themes emerged from these gaps and research needs focusing on (1) elucidating adaptations of iron homeostasis in pregnancy and early infancy including their mechanisms, responsiveness to iron status, interaction with genetic and ethnic factors and implication’s for the differential prioritization of iron to developing tissues and hematopoiesis; (2) improving the assessment of iron status particularly in these two vulnerable periods including the measurement uncertainties, need for indicators across the full continuum of iron status that are adjustable or independent of inflammation; (3) evaluating iron status relative to maternal and infant health outcomes, especially non-hematologic outcomes; and (4) determination of short and long term beneficial and adverse health outcomes, especially non-health outcomes such as GDM, LBW, SGA, postnatal growth and DOHaD, with iron supplementation of iron-replete pregnant women and young children [ 45 , 48 ]. In Figure 1 , an analytic framework of these knowledge gaps and research needs is depicted along the pathway from screening to supplementation to outcomes.…”
Section: Implications For Research and Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Bunula birlikte askorbik asit demir emilimini artırdığından bazı demir takviyeleri C vitamini içermesine rağmen, portakal suyu genellikle demir desteği alan gebelere önerilir. Vejeteryan gebelere; fasulye, mercimek, ıspanak, tam buğday ekmekleri, bezelye, kuru kayısı, kuru erik ve kuru üzüm gibi demir içeriği yüksek gıdaları tüketmeleri için teşvik edilmelidir (3,10,17,18). (3,8,20,21).…”
Section: Diyet Desteğiunclassified
“…The evidence supports the effectiveness of routine iron supplementation during pregnancy for improving maternal haematological indices, but the clinical significance for pregnant women and their newborns remains unclear (Brannon, Stover, & Taylor, ; Brannon & Taylor, ; Cantor, Bougatsos, Dana, Blazina, & McDonagh, ; Demuth, Martin, & Weissenborn, ; Marangoni et al, ; O'Brien & Ru, ). Despite this, the WHO recommends universal iron supplements of 30–60 mg/day during pregnancy (WHO, , ).…”
Section: Introductionmentioning
confidence: 99%